ANTIMICROBIAL RESISTANCE OF BULGARIAN ISOLATES MORAXELLA CATARRHALIS DURING THE PERIOD 1999-2018 - Raina Gergova; Rumyana Markovska (Peytchinski Publishing, 2020)
The purpose of this study was to assess the levels of antimicrobial susceptibility during a period of the last 20 years among Moraxella catarrhalis isolates and to evaluate their resistance mechanisms. Material/Methods: A total of 618 Bulgarian clinical significant isolates M.catarrhalis was collected during the period 1999-2018 from patients to assess the current levels of antimicrobial susceptibility and to evaluate the beta-lactam resistance mechanisms. The minimum inhibitory concentrations (MICs) by E-test were determined against: penicillin, ampicillin, amoxicillin+clavulanic acid, cefalexin, cefuroxime, cefixime, cefotaxime, levofloxacin, azithromycin, clarithromycin, tetracycline, sulfamethoxazole + trimethoprim. PCR examination of genes encoding beta-lactamases was done. Results: Almost all (98.88%) of the tested strains M. catarrhalis showed positive cefinase test and were demonstrated elevated MICs and a lack of susceptibility to penicillin, ampicillin and cefalexin. An increase of resistance to cephalosporin of second and third generations (cefixime) was found. Higher MIC values of cefuroxime and cefixime than these of cefotaxime were detected. PCRs revealed that bro-1 genes (94.11%) were more frequent than bro-2. Conclusions: The results of examined 20 years period showed that nearly all Bulgarian isolates of M. catarrhalis in the last years become resistant to penicillins and first generation cephalosporins via beta-lactamases, encoded predominantly by bro-1 gene. An increase of the resistance to members of second and third generation (cefixime) cephalosporin's and slower to other antimicrobials was found. The rapid development of resistance in recent years to the most popular antimicrobial agents affects the recommendations regarding the initial approach to therapy.